ANALYSIS OF INVESTMENT ATTRACTIVENESS OF UKRAINIAN REGIONS - MUNKA, S. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The country's investment attractiveness on the international scene is impossible without comprehensive economic growth in all regions of the country. The imbalance in the development of the regions will inevitably lead to an outflow of domestic and foreign investment capital, insofar as investors assess the risks in general for the country's economy. To prevent negative consequences, scientists are faced with the task of studying the ratings of the investment attractiveness of the regions in order to determine and overcome the disproportions in economic growth.The article is devoted to determining the investment attractiveness of Ukrainian regions. The essence of the concept is revealed and the methodology for determining the investment attractiveness of the region is investigated. The author's approach to determining the investment attractiveness of Ukrainian regions has been developed. The rating of the regions in terms of investment attractiveness has been determined. The most attractive sectors of the national economy for investment have been investigated by regions. Results of research have practical relevance for public authorities in the tasks of developing strategic plan for the development of regions and private investors to enhance investment activity.The purpose of article is to develop a methodology for determining the investment attractiveness of Ukrainian regions in order to create an appropriate rating and identify imbalance in investment development.The study points to imbalance in the development of regions and shows which regions need additional incentives, and which of them have high investment attractiveness. There are identified investment-friendly industries in each region due to the specialization. We see further research in the development of new methods for determining the investment attractiveness of the Ukrainian economy and its components.
Keywords: investment attractiveness of the region; gross regional product; capital investments; investment potential; enterprise; rating